10th Anniversary of Plants—Recent Advances and Perspectives: Volume I (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
10th Anniversary of Plants—Recent Advances and Perspectives is a scientific paper collection specially published on the anniversary of Plants. Covering all major areas of plant science, it is a valuable guide through current achievements and future discoveries in this scientific field.